Bionic Design for Reducing Adhesive Resistance of the Ridger Inspired by a Boar’s Head - Jianqiao Li; Yunpeng Yan; Benard Chirende; Xuejiao Wu; Zhaoliang Wang; Meng Zou (Applied Bionics and Biomechanics, 2017)
The main feature of the boar’s head used to root around for food is the front part, which is similar to the ridger in terms of function, load, and environment. In this paper, the boar’s head was selected as the biological prototype for developing a new ridger. The point cloud of the head was captured by a 3D scanner, and then, the head surface was reconstructed using 3D coordinates. The characteristic curves of the front part of the boar’s head were extracted, and then, five cross-sectional curves and one vertical section curve were fitted. Based on the fitted curves, five kinds of bionic ridgers were designed. The penetrating resistances of the bionic ridgers and traditional ridger were tested at different speeds in an indoor soil bin. The test results showed that bionic ridger B had the best penetrating resistance reduction ratio of 16.67% at 4.2 km/h velocity. In order to further evaluate the performance of the best bionic ridger (bionic ridger B), both the bionic ridger and traditional ridger were tested in a field under the same working conditions. The field results indicate that the bionic ridger reduces penetrating resistance by 6.91% compared to the traditional ridger, and the test results validate that the bionic ridger has an effect on reducing penetrating resistance.